ANALYSIS OF THE LEVEL OF SATISFACTION OF BROILER CHICKEN MEAT CONSUMER IN TRADITIONAL MARKET AND MODERN MARKET IN PONTIANAK CITY (Case Study of Flamboyan Market and Freshmart Supermarket) - Syafii, Abdullah; Kusrini, Novira; Imelda, Imelda (Jurnal Sains Mahasiswa Pertanian, 2019)
ABSTRACTBroiler chicken meat is the most popular meat of the Pontianak community and can be found in traditional markets and modern markets. The way these two type of markets are in maintaining customers is by knowing the level of customer satisfaction. Satisfied customers will certainly make a repeat purchase and can become a regular customer. The Purpose of this study was to determine the suitability between the level of importance of service attributes by consumers and the level of performance provided by retailers/seller (Flamboyan Market and Freshmart Supermarket), so that it can be known the level of customer satisfaction with the quality of services provided by the seller and provide recommendations for alternative improvements. The method used are CSI (Customer Satisfaction Index) and IPA (Importance Performance Analysis) method which are processed using Microsoft Excel software and SPSS Statistic Ver.22.. Questionnaires were distributed were 96 questionnaires, which were given to 48 Flamboyan market respondens and 48 Freshmart Supermarket respondents. The result of CSI method shows a level of customer satisfaction of 74,42% or categorized â€œsatisfiedâ€ for the Flamboyan market, and 81,27% or categorized â€œvery satisfiedâ€ for the Freshmart Supermarket. The result of IPA method shows that some attributes in both places are in various quadrants that require various treatments, such as : need to be increased, reduced, or maintained.Keywords : Broiler Chicken Meat, CSI (Customer Satisfaction Index), Customer Satisfaction, Â IPA (Importance Performance Analysis).